Identification of differentially expressed genes present in the whole blood of Pulmonary Arterial Hypertension patients and control patients: An integrated bioinformatics approach. (2020) - Ezenwa, Chisom; Soremekun, Opeyemi S.; Nashiru, Oyekanmi; Fatumo, Segun
Abstract: Introduction: While Pulmonary Arterial Hypertension (PAH) remains a commonly undiagnosed disease, it remains a life-threatening disease; it is characterized by pulmonary vascular remodelling subsequently leading to heart failure. Different researches have been at the forefront of exploring drugs for treatment and molecular biomarkers for early diagnosis of PAH. Method: ology: In this study, we used an integrated bioinformatics approach to investigate Differentially Expressed Genes (DEG) in the whole blood of PAH patients relative to gender/age matching controls. Microarray dataset of the aforementioned experiment was retrieved from Gene Expression Omnibus (GEO). DEG analysis was carried out with the aid of the limma algorithm in-built in the GEO2R tool. Gene Ontology terms such as molecular function, biological process, cellular component, and pathway were investigated using the online tool Protein ANalysisTHrough Evolutionary Relationships (PANTHER). Protein-Protein interaction network was carried out using STRING. Results: From the analysis, 191 genes were down-regulated while 5 were up-regulated. Some of these genes are implicated in pathways involved in adrenaline and noradrenaline biosynthesis, angiogenesis, EGF receptor signaling pathway, and VEGF signaling pathway. Furthermore, in the ontology of molecular function, these genes are involved in transport activity, catalytic activity, and molecular transducer activity. Interestingly, the angiogenesis, adrenaline, and noradrenaline biosynthetic pathways are heavily involved in the pathogenesis and progression of PAH. Furthermore, the gene products of these predicted genes were also explored. Conclusion : The gene products (proteins) of these DEGs can be further explored as potential drug targets in the treatment of PAH. This study has also been able to establish the interaction responsible for PAH which can be explored in gene therapy.